Feminist Interpretations of William James - Sullivan, Shannon, 1967-; Tarver, Erin C. (Re-reading the canon., 2015)
"A collection of essays examining the writings of William James. Provides a reinterpretation of pragmatism to devise philosophical resources for pragmatist feminism that challenge sexism and male privilege"--Provided by publisher.